The Chinese Path to Common Prosperity. Issue 1 (2nd January 2022) - Dunford, Michael
ABSTRACT: In China the idea of common prosperity dates back to 1953. After 1979 China chose to let some people and places get rich first to accelerate economic development, with Deng Xiaoping arguing that public property could prevent social polarization. The result was extraordinary sustained economic growth but at the expense of large increases in urban-rural, regional and social inequalities in income and wealth themselves associated with the growth of private capital. In 1999 China started to address urban-rural and regional disparities in the name of common prosperity, while under the leadership of Xi Jinping the emphasis on common prosperity has increased markedly alongside domestic goals relating to innovation, improved governance and ecological and spiritual civilization. Starting in 2020, this course has seen strong government action against the disorderly expansion of private capital, monopolies, speculation and the costs of privately provided education, housing and potentially health, as well as the establishment of a demonstration zone in Zhejiang province to explore ways to address uneven development and reshape the primary, secondary and tertiary distributions of income.